1st International and 2nd National Orthodontic Conference of BOS, Dhaka, Bangladesh, December 27-28, 2012 (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.16005Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 49-50